The Guardian Ancestors. Burials at Bronze Age fortified Sites in the Adriatic Area: Coppa Nevigata and the Istrian Hillforts (Archaeologia Adriatica, 2022)
Around the mid-second millennium BC, some inhumations and disarticulated bones were buried in the area of the fortification lines at the Coppa Nevigata settlement (northern Apulia). This funerary custom appears to be anomalous in the context of Bronze Age southern Italy. On the other hand, such a burial location near to a fortification wall mirrors the funerary evidence from Bronze Age hillforts (castellieri/gradine) in Istria, a region that indeed had close relationships with northern Apulia. Evidence from other European regions is also taken into account, in order to evaluate to what extent this phenomenon was a distinctive trait pointing to interaction between the south-western and north-eastern Adriatic and what their nature was. European contexts offer only generic similarities, whereas the consistency of funerary practices at settlements in the Adriaticarea, based on a close association with defensive lines, appears to be far from random.